Advertisements As Teaching Materials: Discourse And Gender Perspective - Ngasbun Egar; Dias Andris Susanto (International Conference on Science, Education, and Technology, 2021)
Teaching systemic functional linguistics for postgraduate students needs to be more creative and contextual catching with the language used in business matters. Engaging language Metafunction and Indonesian advertisements create alternative teaching materials for lecturers. This research problem is that how do students reveal the meanings of ideational and interpersonal constraints with the discourse and gender in which exists in Javanese culture. Writers used descriptive content analysis to design this research with having 10 popular Indonesian advertisements along in some media. The result shows that the material process is more dominant used to inform the products by filling many verbal words on its texts. Otherwise, interpersonal meaning uses a more declarative mood to present and provide the benefit and quality of its product by delivering more predicators on its texts. Indonesian students' discourse perspective portrays that ideology and cultural background is the main reason they chose the advertisements as the teaching materials to discuss. Moreover, gender perspective realizing that females prefer discussion about cosmetics products while males explore more on automotive products. The conclusion draws advertisements designer inserting texts within products for exchanging information to get the people’s interest and benefit through using proper texts, discourse, and gender perspective to perform the perfect of its product. The writers suggest that analyzing texts used in advertisements might be the best early practice to explore language metafunction.